Family-Focused Practices in Addictions: A Scoping Review. Issue 1 (2nd January 2021) - Kourgiantakis, Toula; Ashcroft, Rachelle; Mohamud, Faisa; Fearing, Gwendolyn; Sanders, Jane
ABSTRACT: Family-focused practices are a critical part of substance use and problem gambling treatment. This scoping review mapped empirical studies on family interventions in addictions and we selected 95 articles that met inclusion criteria. Studies used quantitative (82%), mixed (14%), and qualitative (5%) methods. There were three categories of family-focused interventions: (1) interventions for couples (41%), (2) family interventions which include the individual with the addiction-related concern (35%), and (3) family interventions that focus on the family's needs (23%). Selected studies report that family involvement reduces distress, enhances coping skills, and improves family functioning. Researchers recommend more culturally adapted interventions and increased training for social workers and other service providers on working with families in addiction treatment.